Psammoneis fujianensis sp. nov. (Bacillariophyceae), A New Epipsammic Diatom Species from Fujian, China - Qiu, Yu; Liu, Honghan; Gao, Yahui; Liang, Junrong; Sun, Lin; Chen, Changping (Phytotaxa, 2025)
This study describes Psammoneis fujianensis, a new species of the genus Psammoneis, collected from sand grains in the intertidal zone of Weitou Bay, Fujian Province, China. The specific ultrastructural characteristics of this species were examined using light and scanning electron microscopy. Distinctive characteristics of P. fujianensis include the linear-elliptical valve shape, sparse striae, and C-shaped areolae near the sternum. The ultrastructure of the gelatinous stalk of this species was also observed. We compared the morphological features of P. fujianensis with those of other known species of the genus, including P. japonica, P. pseudojaponica, P. senegalensis, and P. obaidii. This represents the first global record of this species and the first record of the genus Psammoneis in China.